Committed to Diversity. Medicine in a Pluralistic Society - Steger, Florian; Orzechowski, Marcin (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
The increasing social and cultural diversity of modern society leads to important ethical challenges. A special area of tension arises when the concepts of individual freedom of choice and pluralistic social order have to be reconciled with the obligations of medicine in the sense of responsible and caring action. Based on the examples of religiously motivated circumcision and transsexuality, the authors analyze the confrontations between the needs of the patients and the ethical principles of modern medicine. In this, apparent becomes the special role that doctors play in weighing the values of a pluralistic social order on the one hand and the principles of self-determination, non-harm, benevolence and social justice on the other hand. Doctors and healthcare professionals should have the appropriate skills to be able to perceive existing religious or gender-specific differences and individual circumstances and to integrate these into their decisions and actions.